2023
DOI: 10.1287/mnsc.2022.4339
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Investing on Charitable Donations

Abstract: We examine the impact of social investing on charitable donations using a unique data set consisting of investment behaviors and donation transactions for more than 10,000 customers of an investment app platform. We find that investors switching to a recently introduced social fund reduced their donations, mainly in charities supporting causes similar to those of the social fund. However, 79% of the investors that switched to the social fund did not donate before switching, so the social fund attracted more pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…They neither decrease nor increase their donations after thinking of their good investment fortune. Prior literature has found that after investing in ESG funds, investors on average reduce their charitable donations [4] . These investors see ESG funds as an alternative to achieving social goals, and once they allocate more of their giving budget to ESG investing, they allocate less to donations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They neither decrease nor increase their donations after thinking of their good investment fortune. Prior literature has found that after investing in ESG funds, investors on average reduce their charitable donations [4] . These investors see ESG funds as an alternative to achieving social goals, and once they allocate more of their giving budget to ESG investing, they allocate less to donations.…”
Section: Discussionmentioning
confidence: 99%
“…Some investors may invest in ESG funds solely because they believe these funds will outperform other investments, without being motivated by social impact. Moreover, evidence suggests that an investment in ESG can lead investors to donate less to charity [4] . Investors may view ESG investing as a substitute for donations, and thus donate less after investing in ESG funds.…”
Section: Introductionmentioning
confidence: 99%
“…where D ms is a delay in milliseconds in the range 1000 ≥ D ms ≤ 4999 and random( ) generates a random value in the range [0, 1].…”
Section: System Setupmentioning
confidence: 99%
“…This involves monetary gifts, charitable giving, fundraising, lobbying, and awareness campaigns. Charity organizations bring positive change with significant impact on people and society by devoting time, resources, and energy to helping communities [1] and causes in need. The Sustainable Development Goals (SDGs) to eradicate poverty, achieve social equality, safeguard the environment, and promote peace and prosperity were set by the United Nations in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-investing platforms fall under the umbrella of democratized investing. This category includes micro-investing 8 as well as peer-to-peer (P2P) lending 9 , micro-financing 10 and crowdfunding 11 , 12 . These emerging platforms provide a wider portion of the population access to mainstream financial resources (e.g., financially vulnerable consumers 13 ), thereby enabling investors to have a voice in capital allocation.…”
Section: Introductionmentioning
confidence: 99%